IMPROVING PHYSICAL DEVELOPMENT OF CHILDREN BY TEACHING THEM TO SWIM FROM INFANCY - Norkobilov M. N; Tashpulatov F.A; Khamraeva Z.B (Proximus Journal Publishing, 2024)
The main form of organizing and conducting swimming lessons is a group lesson, which embodies the entire educational process. The task, content and direction of each lesson are determined based on the tasks and educational material set before the course, as well as the knowledge and skills of the participants acquired in the previous lessons. The lesson plan is created on the basis of tasks and methods of training. It is conditionally divided into three parts - preparatory, main and final parts. In the preparatory part, the task of organizing and preliminary training of the participants is carried out. It involves organizing students (sorting, reporting, sorting, etc.), briefly returning what has been passed, correcting general and personal mistakes, explaining and demonstrating new educational material, performing previously learned and new auxiliary exercises and, Finally, there is the exercise of writing, which is necessary for the body of the exercisers to enjoy the success of the exercise.
Keywords: Swimming lessons; Children's health activities